Payments for Agrobiodiversity Conservation Services and the Seed Access Challenge: What role for (community) seed banks in Peru? - Drucker, Adam G.; Ramírez, Marleni; Vernooy, Ronnie (2022)
In Peru, the Ministry of Environment (MINAM) and Regional Governments have shown strong support for Payments for Agrobiodiversity Conservation Services (PACS)-type incentive mechanisms since 2014. In 2019, MINAM began to apply PACS as a central component of its on-going GEF Agrobiodiversity (ABD) project which aims to cover over 150 communities by the end of 2022 in four high diversity Andean regions in Peru.